Heterozygous mutation of the splicing factor Sf3b4 affects development of the axial skeleton and forebrain in mouse. Issue 5 (14th January 2020) - Yamada, Takahiko; Takechi, Masaki; Yokoyama, Norisuke; Hiraoka, Yuichi; Ishikubo, Harumi; Usami, Takako; Furutera, Toshiko; Taga, Yuki; Hirate, Yoshikazu; Kanai‐Azuma, Masami; Yoda, Tetsuya; Ogawa‐Goto, Kiyoko; et al.
Abstract: Background: Splicing factor 3B subunit 4 ( SF3B4 ) is a causative gene of an acrofacial dysostosis, Nager syndrome. Although in vitro analyses of SF3B4 have proposed multiple noncanonical functions unrelated to splicing, less information is available based on in vivo studies using model animals. Results: We performed expression and functional analyses of Sf3b4 in mice. The mouse Sf3b4 transcripts were found from two‐cell stage, and were ubiquitously present during embryogenesis with high expression levels in several tissues such as forming craniofacial bones and brain. In contrast, expression of a pseudogene‐like sequence of mouse Sf3b4 ( Sf3b4_ps ) found by in silico survey was not detected up to embryonic day 10. We generated a Sf3b4 knockout mouse using CRISPR‐Cas9 system. The homozygous mutant mouse of Sf3b4 was embryonic lethal. The heterozygous mutant of Sf3b4 mouse ( Sf3b4 +/− ) exhibited smaller body size compared to the wild‐type from postnatal to adult period, as well as homeotic posteriorization of the vertebral morphology and flattened calvaria. The flattened calvaria appears to be attributable to mild microcephaly due to a lower cell proliferation rate in the forebrain. Conclusions: Our study suggests that Sf3b4 controls anterior‐posterior patterning of the axial skeleton and guarantees cell proliferation for forebrain development in mice. Key Findings: We generated a Sf3b4 knockout mouse. Sf3b4 +/‐ mouse exhibited homeotic posteriorization of the vertebral morphology and flattened calvaria. The flattened calvaria in Sf3b4 +/‐ mouse appears to be attributable to mild microcephaly due to a lower cell proliferation rate in the forebrain.